Etiologies and outcomes of pleural effusions in patients with systemic lupus erythematosus - Nattawan Palavutitotai (2018)
Copyright © 2014 by Lippincott Williams & Wilkins. Background: Pleuritis is the most common pulmonary manifestation in systemic lupus erythematosus (SLE). In Thailand, the incidence of tuberculosis (TB) is high; moreover, treatment with immunosuppressive agents increases the risk for TB infection.Objective: The objective of this study was to examine the clinical manifestations, etiology, management, and outcomes of patients with SLE and pleural effusion in an area for TB.Methods:We studied adults satisfying the American College of Rheumatology classification criteria for SLE who presented with pleuritis between 2002 and 2010. Pleuritis was defined as having 1 of 3 of the following criteria: typical pleuritic chest pain, pleural rub, and clinical or radiological evidence of pleural effusion.Results: A total of 119 patients with 127 episodes of pleuritis/pleural effusion were included. Pleuritis was the first presentation in 47 episodes (37%) and was found accompanied with pericarditis for 16%.Most patients (81%) had active SLE in other systems. The causes of pleural effusion included lupus pleuritis (52%), tuberculous pleuritis (9%), parapneumonic effusion (7%), and transudate (15%). The diagnosiswas inconclusive in 17%. The diagnosis of lupus pleuritiswasmade by a clinical diagnosis (47%) and by excluding other causes frompleural fluid analysis or biopsy (53%). Most patients with lupus pleuritic responded well to corticosteroid therapy.Conclusions: Lupus pleuritis is still the most common cause of pleural effusion in SLE and often reflects its disease activity. The diagnosis of lupus pleuritis is a clinical diagnosis or is performed by excluding other conditions. The treatment outcomes of lupus pleuritis are generally good.